2019
DOI: 10.1007/s11892-019-1238-y
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas Transplantation from Donors after Circulatory Death: an Irrational Reluctance?

Abstract: Purpose of Review Beta-cell replacement is the best therapeutic option for patients with type 1 diabetes. Because of donor scarcity, more extended criteria donors are used for transplantation. Donation after circulatory death donors (DCD) are not commonly used for pancreas transplantation, because of the supposed higher risk of complications. This review gives an overview on the pathophysiology, risk factors, and outcome in DCD transplantation and discusses different preservation methods. Recent Findings Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…It is important to consider how this analysis should change transplant practices. This study strongly supports an expansion in the use of SPK transplants from controlled DCD donors 36 . In countries with relatively high DCD donor pancreas utilization rates such as the UK, the above data suggest that a careful increase in DCD donor age criteria would also be appropriate.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It is important to consider how this analysis should change transplant practices. This study strongly supports an expansion in the use of SPK transplants from controlled DCD donors 36 . In countries with relatively high DCD donor pancreas utilization rates such as the UK, the above data suggest that a careful increase in DCD donor age criteria would also be appropriate.…”
Section: Discussionsupporting
confidence: 73%
“…This study strongly supports an expansion in the use of SPK transplants from controlled DCD donors. 36 In countries with relatively high DCD donor pancreas utilization rates such as the UK, the above data suggest that a careful increase in DCD donor age criteria would also be appropriate. In those countries with limited (or no) experience of pancreas transplantation from DCD donors, it is understandable that a more cautious initial approach may wish to be taken, seeking to limit likely risk factors for reduced pancreas graft survival such as donor age >50 years, pancreas CIT >12 h, pWIT <30 min, and prolonged anastomosis times while experience with this donor source accrues.…”
Section: Discussionmentioning
confidence: 97%
“…In the setting of donation after circulatory death (DCD), the use of young controlled DCD donors was not considered a contraindication to pancreas transplantation, as evidence showed that when donor age is <40 years, results are good irrespective of donor source (i.e., DCD or DBD). 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 …”
Section: Discussionmentioning
confidence: 99%
“…In the discussion, experts underscored that the use of pediatric donors of low body weight (<15 kg) may increase the risk of technical failure, while a BMI < 35 kg/m 2 reduces the impact of obesity. In the setting of donation after circulatory death (DCD), the use of young controlled DCD donors was not considered a contraindication to pancreas transplantation, as evidence showed that when donor age is <40 years, results are good irrespective of donor source (i.e., DCD or DBD) 117–124 …”
Section: Discussionmentioning
confidence: 99%
“…These suboptimal donors are defined in PTx as those with a body mass index of greater than 30kg/m 2 and outside the range of <10 to >45 years of age [3]. Donation after circulatory death (DCD) status is also regarded as risk factor for accruing ischaemic injury during preservation [4].…”
Section: Introductionmentioning
confidence: 99%